Venezuela then and now How did the Chavezian era change the Latin-American country’s economy? - Csiba Betti Kata (2015)
Venezuela has gained considerable attention in the past few years, especially since the demonstrations of early 2014. The case of Venezuela has special significance for those from the former Eastern bloc as it is interesting to observe the consequences of 21st-century socialism. The study also holds relevance for other (European) countries that are experiencing a political shift away from traditional central forces as it points out the issues Venezuela experienced that could be sidestepped. The aim of this work is to determine the extent to which Hugo Chávez’ economic, social and political legacy is responsible for the current struggle of the country. The main question regarding Chávez’ (social) policies still to this day remains whether they were ef-ficient in reducing poverty and the thesis aims to find an answer to the above mentioned assumption. Most previous works focus on only a restricted topic such as the social policies of the Chávez-government or are of greater extent and analyse the situation of the entire con-tinent – this work, however, attempts to provide readers with a chronological description of Venezuela’s past and present and outline the possibilities in the future. The author is strongly convinced that only by knowing the way Chávez could gain power is it possible to understand the ex-colonel’s popularity which explains how he could remain in power despite his controversial governance. Only after describing the situation does the study go on to evaluate the economic, social and foreign policies of the Chávez-government and draw consequences related to recent events both within and outside Venezuela. For the sake of impartiality, the author used several (at times contradicting) sources and considered opposing opinions to make sure the data in the thesis is trustworthy and unbiased. The conducted research is strictly theoretical based on credible sources that are free from political influences; at times, it used manipulated data in comparison with offi-cial information only to show the extent of governmental corruption in Venezuela. Results show that the decrease in the poverty rate is neither as substantial nor as permanent as was stated by the Venezuelan government, meaning that the first and fore-most goal of the Chávez-government was not reached. Also, even though the incumbent president’s mismanagement contributed to the current problems, it is obvious that the lega-cy of the Chavez-government is one of the main causes of recent troubles, together with external negative impacts. These results imply that a break from the current governing sys-tem is much needed in Venezuela and it would better bring along structural reforms.